Low Flow Practice for Laparoscopic Colorectal Surgery in Pediatric Patients - Yadikusumo, Andrian; Senapathi, Tjokorda Gde Agung; Shintya Dewi, Dewa Ayu Mas; Pradhana, Adinda Putra; Sumanti, Alan F. A. (Bali Journal of Anesthesiology, 2018)
Low flow anesthesia and laparoscopic technique in pediatric patients are kinds many kind of modern medical field development.Â  Both technique were made to support environment friendly, safety, and comfortable anesthesia practice for patients.Â  In three cases presented in this case series, laparoscopy was done in all three cases (two digestive cases, and one urology case).Â  All three cases performed with general anesthesia by low flow anesthesia technique with volatile sevoflurane combined with caudal block regional anesthesia.Â  In all those cases, no morbidity was found after anesthesia or operation that influence in patientâs outcome.Â  Improvement in outcome of pediatric patients was seen with low flow anesthesia technique, which are significant reduction of volatile used, faster wake up time, and reduction of agitation condition after anesthesia.